DEVELOPING THE BIOLOGY DIGITAL COMICS AS THE MEDIA FOR LEARNING OF HUMAN CIRCULATORY SYSTEM - Sari, Anggi Wulan; Djulia, Ely; Edi, Syahmi (Smart Education, 2025)
Abstract: The purpose of this study was to create digital comics on biology and assess their suitability and effectiveness as a teaching tool for the human circulatory system for eleventh graders in terms of learning outcomes. The approach used an R&D model that was modified from the Borg and Gall model. Subjects included pupils from SMA Negeri 1 Kisaran and SMA Negeri 4 Kisaran. The data of interviews, questionnaires, and multiple choices were obtained. The findings demonstrated the validity of the eligibility level of the biology digital comics created; 94% of the material experts, 89% of the instructional design experts, and 94% of the layout experts evaluated the comics. With an average score of 88%, the created educational materials that were evaluated by students fell into the very good category. In the meantime, the effectiveness level of biology digital comics with an N-Gain value of 0.57 in a moderate category and the eligibility level gained from the teachers was 90% in a very good category. Keywords: Learning media, digital comics, biology, circulatory system Abstrak: Tujuan dari penelitian ini adalah membuat komik digital mata pelajaran biologi dan menilai kesesuaian dan efektivitasnya sebagai alat bantu pengajaran sistem peredaran darah manusia untuk siswa kelas XI ditinjau dari hasil belajar. Pendekatan yang digunakan adalah model R&D yang dimodifikasi dari model Borg and Gall. Subyek penelitiannya adalah siswa SMA Negeri 1 Kisaran dan SMA Negeri 4 Kisaran. Data diperoleh melalui wawancara, angket, dan pilihan ganda. Temuan tersebut menunjukkan validitas tingkat kelayakan komik digital biologi yang dibuat; Komik dinilai oleh 94% ahli materi, 89% ahli desain pembelajaran, dan 94% ahli tata letak. Dengan skor rata-rata sebesar 88%, materi pendidikan yang dibuat dan dinilai oleh siswa masuk dalam kategori sangat baik. Sedangkan tingkat keefektifan komik digital biologi dengan nilai N-Gain sebesar 0,57 berada pada kategori sedang dan tingkat kelayakan yang diperoleh dari guru sebesar 90% berada pada kategori sangat baik. Kata kunci: Media pembelajaran, komik digital, biologi, sistem peredaran darah